Company Financial Performance Evaluation Information - Rufaida, Alfi Maulissa Rufaida (JAKI : Jurnal Akuntansi, 2024)
This article aims to analyze the company's financial performance evaluation information. The method used in this article is a qualitative method. The data source for this research was obtained from written sources related to the concept of context and nature of entrepreneurship. The type of data used in this article is qualitative data. The data collection technique was carried out by searching the literature. The data analysis technique in this article uses narrative techniques. Based on the literature review that has been carried out, the company's financial performance evaluation information is financial performance. Financial performance is a representation of the company's financial condition in a certain accounting period, including aspects of collecting and distributing funds. Usually, this performance is measured through indicators of capital adequacy, liquidity and profitability. Financial performance information is very important for a company because as a means of identifying risks and accurate financial performance information can provide long-term sustainable growth for the company.